2008
DOI: 10.1021/cm7026866
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoparticle Architecture Determines Radiative Properties of Encapsulated Fluorophores

Abstract: Silica nanoparticles with embedded fluorescent molecules are used in a variety of applications requiring the observation of single nanoprobes. We describe a class of fluorescent, core–shell silica nanoparticles with a radius of ∼15 nm, narrow particle size distribution, and controlled internal architecture. Particles covalently encapsulating multiple rhodamine molecules are over 20 times brighter than the single dye molecule in water. The photophysical behavior of rhodamine can be manipulated by small changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
321
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(341 citation statements)
references
References 41 publications
16
321
1
3
Order By: Relevance
“…Both the solute GS and EES FFs were parameterized by the JOYCE package, 50,51 through a least square minimization of the functional I intra (5) where N geom is the number of the sampled conformations, Q K is the K th normal coordinate and U g is the QM computed energy in the g th geometry, with respect to the absolute minimum (g = 0). The QM Hessian matrix H KL and the FF Hessian are evaluated at g = 0.…”
Section: Ff Parameterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the solute GS and EES FFs were parameterized by the JOYCE package, 50,51 through a least square minimization of the functional I intra (5) where N geom is the number of the sampled conformations, Q K is the K th normal coordinate and U g is the QM computed energy in the g th geometry, with respect to the absolute minimum (g = 0). The QM Hessian matrix H KL and the FF Hessian are evaluated at g = 0.…”
Section: Ff Parameterizationmentioning
confidence: 99%
“…Organic dyes 1 have recently attracted a growing attention, thanks to their wide range of applications, that covers different fields in both materials [2][3][4][5][6][7][8][9][10][11] and life sciences. [12][13][14][15] In particular, the high selectivity and specificity of some fluorescent molecules in detecting particular molecular targets and/or in modulating the responses to different external stimuli are often exploited to investigate the structural and dynamic properties of a wide variety of complex systems like, e.g., polymeric materials, DNA structures, protein conformations or lipid aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They incorporated hydrophobic rhodamine 6G molecules inside the SiNPs by using two compounds as precursors with a different lipophilicity i.e., more hydrophobic phenyltriethoxysilane (PTES) [PhSi(OCH 3 )] which keeps the organic dye in the silica matrix and [Si(OR) 4 ] (TEOS) which can turn into a hydrophilic comopound, thus it allows obtained SiNPs to be dispersed in an aqueous solution [373]. All SiNPs have approximately the same size and composition but selected dyes (e.g., fluorescein, pyrene) [374,375] might exhibit different photophysical properties [376]. The silica matrix provides embedded dyes an effective barrier to protect them against the surrounding environment and both photobleaching and photodegradation phenomena can be minimized [377].…”
Section: Silica Nanoparticles For Bioimaging In Therapymentioning
confidence: 99%
“…Many studies have been reported about dye-doped silica nanospheres, and the increase of fluorophore emission intensity and photo stability when the dye molecule is entrapped in the solid structure are effects that have been observed. [5][6][7] The flavonoid quercetin forms complexes with Al 3+ resulting in species with high fluorescent quantum yield because excited state intramolecular proton transfer (ESIPT) process in quercetin is inhibited. 8 These complexes have been studied in methanolic solution 8,12 and they can be interesting systems to investigate the interaction of silica nanoparticles and to be used as probes for Al In the present work, the quercetin-Al 3+ complexes are studied in two types of colloidal silica matrices, using steadystate and time-resolved fluorescence and UV-Vis absorption techniques.…”
Section: Introductionmentioning
confidence: 99%